A COMPARATIVE CLINICAL STUDY ON THE EFFECTIVENESS OF BHARANGYADI CHOORNA AND VYAGHRI CHOORNA IN TAMAKA SWASA (BRONCHIAL ASTHMA) (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda classics mentioned various types of Swasa and Tamaka Swasa is one among them. Tamakaswasa is manifested by aggravated Pranavayu by the obstruction of Kapha. In this case treatment should be to clear out Pranavaha srotas, pacify Vata and remove the blockage due to Kapha. In modern science Tamaka Swasa is correlated with Bronchial Asthma. It’s a chronic inflammatory disorder of the airways in which the chronic inflammation causes an associated increase in airway hyper responsiveness that leads to recurrent episodes of asthmatic exacerbation. Modern science has no permanent cure of Tamaka Swasa, that’s why it is necessity to search herbal and herbo-mineral preparations for the treatment of disease. Present Study was conducted to reduce the symptoms of Tamakaswasa. Bharangyadi Choorna and Vyaghri Choorna have the properties of Kapha Vata hara, Agni Deepana, Pachana, Anulomana, Srotoshodhana, anti-asthamatic and anti-inflammatory property. Materials and Method: Patients who have symptoms of Tamakaswasa fulfill the inclusion criteria were given with Bharangyadi Choorna 4gm thrice a day along with Ardraka Swarasa as Anupana in the trail group i.e., group A and Vyaghri Choorna 4gm thrice a day along with honey as Anupana in the control group i.e. group B. It is a comparative clinical study with 30 patients in each group for 30 days. Analyzing the signs and symptoms, PEFR after each 10 days, Wilcoxon test was done for comparing the effectiveness of treatment between two groups. Comparative analysis of the overall effect of the treatments in both the groups was done by statistically done by Mann-Whitney test. Results: There was statistically significant change in all the signs and symptoms and PEFR after treatment and follow up. All the signs and symptoms have P ≤ 0.05. Conclusion: Bharangyadi Choorna has shown highly significant reduction in the symptoms like Swasakrichratha, Peenasa, Kasa, Ghurghuraka, Krichrabhashana, Shushkasya and PEFR. On comparison between the two groups, Bharangyadi choorna showed a better result in improvement of symptoms- Swasakrichratha, Peenasa, Kasa, Ghurghuraka, Krichrabhashana, Shushkasya and objective parameter- PEFR. Hence H2 hold good.